(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
: This article provides a comprehensive overview of the IELTS Listening section, outlining the different types of questions and offering practical examples and tips for each. It highlights the key question formats such as multiple-choice, matching, flow- chart completion, and short-answer questions, offering readers clear explanations and strategies to tackle each one effectively. The article emphasizes the importance of practice, listening comprehension, and time management, encouraging readers to familiarize themselves with different accents, content types, and paraphrasing techniques. The conclusion underscores the significance of preparation for success in the IELTS Listening test, ultimately improving both test performance and real-world listening skills. This resource is useful for IELTS candidates aiming to improve their listening proficiency and achieve a high score in the exam.